Using an in-situ Simulation Model to Identify Deviations from Guideline-Based Management of Pediatric Status Epilepticus in Community Emergency Departments - Firn ET; Jonas R; Douglass LM; Walsh BM (Open Access Emergency Medicine)
Eliza T Firn, Rinat Jonas, Laurie M Douglass, Barbara M Walsh Department of Pediatrics, Boston University Chobanian & Avedisian School of Medicine, Boston Medical Center, Boston, MA, USACorrespondence: Eliza T Firn, Email etszuch@gmail.comBackground: Children with epilepsy are often presented to Community Emergency Departments (CEDs) for acute treatment of status epilepticus (SE). Timely medical management is imperative to prevent morbidity and mortality, and adherence to evidence-based guidelines improves outcomes for high stakes/low frequency events. Barriers to guideline adherent management in the CED setting are understudied; in-situ simulation (ISS) can be used to identify gaps in care for events such as pediatric SE.Objective: The primary objective was to assess for deviations from evidence-based guidelines in the management of pediatric SE. A secondary objective was to explore potential barriers to practice within the evidence-based guidelines.Methods: We conducted a prospective observational ISS pilot study examining representative CED teams caring for a simulated child in SE. The primary outcome was overall adherence to the pediatric SE guidelines as measured by 12 metrics: 5 non-pharmacologic (for example: delays in vital sign assessment, failure to time seizure) and 7 pharmacologic (for example: incorrect benzodiazepine dose, delay in benzodiazepine administration or escalation to antiseizure medication). Additional metrics including provider knowledge (recognition of status epilepticus) and resources (antiseizure medications stocked) were analyzed as process measures. We enrolled 4 interprofessional teams at 4 participating ED sites.Results: Overall, 0 of the 4 teams adhered to all 12 metrics. A barrier to timely administration of benzodiazepines for two of the sites came from attempting IV access repeatedly. No team referenced an up-to-date treatment algorithm based on current evidence-based guidelines.Conclusion: Standardized ISS scenarios identified variability in adherence to the pediatric SE guideline across a pilot sample of local CEDs. Barriers to guideline-adherent care occurred at both individual and systems levels. The study was limited in scope to 4 pilot sites.Keywords: simulation, pediatric, status epilepticus